2017
DOI: 10.11648/j.sjph.20170502.21
|View full text |Cite
|
Sign up to set email alerts
|

Decentralisation of Health Systems and the Fate of Community Health Fund in Tanzania: Critical Review of High and Low Performing Districts

Abstract: Abstract:The deterioration of health services provision in Tanzania from 1980s to 1990s made decentralization of health service provision through the Health Sector Reform (HSR) a necessity. HSR aimed at bringing better utilization of scarce resources, improved quality of health services, increasing user access and cutting rising costs. It is through HSR that health insurance schemes were introduced. Community Health Fund (CHF) came as a result of such efforts. The efficiency and effectiveness of CHF rests on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…8 of 1999 established the today used NHIF and started is operations in June 2001 [ 1 , 10 , 11 ]. Through the NHIF, public formal sector employees are paying a are required to contribute 3 percent of a monthly’s salaries while government also contribute same share to make a total of 6% with not more than 5 other members of the family as a dependent [ 8 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…8 of 1999 established the today used NHIF and started is operations in June 2001 [ 1 , 10 , 11 ]. Through the NHIF, public formal sector employees are paying a are required to contribute 3 percent of a monthly’s salaries while government also contribute same share to make a total of 6% with not more than 5 other members of the family as a dependent [ 8 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been frequently reported that households are unable to join the scheme due to poor community engagement and high premium rates. 6,[8][9][10][11]13 Engagement of the community through communication and awareness about CHF reforms was not done well at the community level between the community members and CHF implementing partners. Speci cally, community engagement assumed a top down approach, whereby community members were mainly involved during the implementation process.…”
Section: Discussionmentioning
confidence: 99%
“…In a Tanzanian decentralized health care system, HFGCs were introduced in 1999 during the health sector reforms [21]. The HFGCs are composed of elected community members and health facilities in charge [22].…”
Section: Introductionmentioning
confidence: 99%